Analisa Kerentanan Seismik pada Struktur Eksisting Menggunakan Metode Rapid Visual Screening di Kota Malang - Dzul Fikri Muhammad; Syahidah Fani Nastiti; Agil Fitri Handayani; Gading Chempakadewi; Muhammad Hamza (G-Tech: Jurnal Teknologi Terapan, 2023)
Several tectonic plates and a string of active volcanic mountain ranges encircle the Indonesian country, making a considerable part of Indonesia susceptible to both tectonic and volcanic earthquakes. The Indonesian National Standardization issued the latest earthquake regulations in 2019, replacing the regulations from 2012. As a result, the seismic map's PGA, Ss, and S1 values rose in comparison to the map from 2010.. With these elevated values, the regions in Indonesia become more vulnerable to earthquakes. The city of Malang itself falls within the moderate seismicity zone or is categorized as having a moderate level of vulnerability. The new regulations can be directly implemented for new buildings. To find out if they can handle the new seismic loads, existing structures must also be assessed.. This research focuses on assessing the vulnerability of old buildings to the new seismic loads in accordance with the updated regulations, using rapid visual screening. The results indicate that the examined buildings are still considered capable of withstanding the new seismic loads.